1974
DOI: 10.1002/bit.260160204
|View full text |Cite
|
Sign up to set email alerts
|

The rheology of mycelial broths

Abstract: SummaryAn experimental investigation on the rheology of penicillin broths was undertaken in order to obtain more understanding of this important aspect of the fermentation process. The measuring technique consisted in observation of the torque exerted upon a rotating turbine impeller. The experimental data were interpreted in terms of a model which basically is a synthesis of a known relationship for the rheological behavior of printing ink (Casson equation) and some considerations analogous to the rheological… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
38
0

Year Published

1976
1976
2010
2010

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 109 publications
(40 citation statements)
references
References 8 publications
2
38
0
Order By: Relevance
“…The averaged percentage error on (K/C ␣ m ) calculated in this way was 34%. This plot illustrates the reason for the poor quality of correlations based purely on biomass concentration, which have been reported in the literature (Carilli et al, 1961;Roels et al, 1974;Solomons and Weston, 1961;Takahashi and Yamada, 1960). These necessarily used an average value for the constant in correlation (1), applied to all morphologies and fermentation times.…”
Section: Resultsmentioning
confidence: 81%
See 2 more Smart Citations
“…The averaged percentage error on (K/C ␣ m ) calculated in this way was 34%. This plot illustrates the reason for the poor quality of correlations based purely on biomass concentration, which have been reported in the literature (Carilli et al, 1961;Roels et al, 1974;Solomons and Weston, 1961;Takahashi and Yamada, 1960). These necessarily used an average value for the constant in correlation (1), applied to all morphologies and fermentation times.…”
Section: Resultsmentioning
confidence: 81%
“…This is due in part to the large innate variability that exists in the morphology of mycelia grown in submerged cultures (Metz et al, 1981), which makes its characterization difficult. Quantitative studies include the work of Roels et al (1974), Metz et al (1979), Kim and Yoo (1992), Liu and Yu (1993), Fatile (1985), Olsvik et al (1993), Olsvik and Kristiansen (1994), Mohseni and Allen (1995), Tucker and Thomas (1993), and Tucker (1994). Only the last five of these used image-analysis methods for rapid and accurate characterization of mycelial morphology-methods that greatly extend the amount and type of data that can be obtained.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…4), with biomass concentration having a progressively greater impact on torque as it increased. It has been suggested that an increase in mycelial interactions result in network formation causing mycelial suspensions to become more viscous and that the impact of these interactions is exaggerated as biomass concentrations increase (Roels et al, 1974;Metz, 1976;Oolman and Blanch, 1986). It was also noted, however, that increases in biomass had less influence on torque the more highly branched the filaments were (Fig.…”
Section: Discussionmentioning
confidence: 89%
“…These earlier studies also reported differences in the type of rheological behavior observed in various broths. The techniques used for determination of the non-Newtonian nature of the broths have recently been discussed by Roels et al 4 and these may account for the varying reports of Bingham or power-law behavior.…”
Section: Introductionmentioning
confidence: 99%